RANCANGAN POSTER BIOLOGI SMA KELAS X PADA MATERI BAKTERI - Rahmi, Zunnur; Sayuti, Irda; Wulandari, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the potential of poster design in class X bacterial high school learning material. This research was conducted at the Binawidya Riau University in November 2019-februari 2021. This research was conducted in 2 stages: the experimental stage and the second stage is Poster Design that is analysis of the potential development of high school learning media Bacteria class X material. The study used an experimental method of descriptive qualitative research design. Based on the potential analysis, it was found that lypolitic bacteria isolated from palm oil mill effluent can be used as a poster design of class X bacterial material for SMA 3.5 KD.Key Words: Poster, Bacteria